The Impact of Regularity of Primary Care on Emergency Department Presentations and Hospital Admissions - Youens, David (Curtin University, 2022)
This thesis examines the impact of regular contacts with the general practitioner, and continuity of care with the same general practitioner, on use of hospital and emergency department services among patients with chronic conditions. Through analysing existing clinical and administrative health data, this thesis assesses several causal pathways by which primary care may influence downstream hospitalisation outcomes, and expands upon existing research in this area through testing alternative research designs and analysis methods.